Mental Health Outcomes, Parenting Skills and Family Functioning of Adult and Family Treatment Court Participants - Guastaferro, Wendy P. (2019)
Background: Parental substance use places children at risk for poor social, emotional, and behavioral outcomes. Many parents with substance use disorders (SUD) are treated through accountability drug courts including adult drug courts (ADC) through the criminal justice system and family drug treatment courts (FTC) through the child welfare system. Little is known about the children of parents who participate in treatment through adult drug courts, which could serve as an important treatment venue for improving child outcomes. Children treated through family treatment courts are often the center of treatment. This research compared outcomes of parents and children involved in adult drug and family treatment courts. Methods: Participants were 105 drug court clients (80 from ADC; 25 from FTC) from four Georgia based drug courts. Participants completed computerized interviews containing a variety of measures focusing on adult mental health, parenting behaviors and communication, and child mental health and behavior. Results: Parents in FTC compared to those in ADC reported greater social support (p =.05) and better family functioning (p =.03). Parents in ADC reported poorer parental involvement and poorer monitoring of children than FTC, but no differences in positive parenting (p =.13), inconsistent discipline (p =.27), or child abuse potential (total risk > 9, p =.42; total risk >12, p =.37). Regarding mental health, ADC parents reported a greater number of symptoms or poor mental health than FTC. No differences were found for parent-child communication skills (p =.38), post-traumatic stress symptom severity (p =.62), or child behavior problems. Conclusions: This data suggests that children of caregivers in drug treatment via ADC are at equal and perhaps greater risk than children of caregivers in FTC because of increased parental risk factors. ADC should consider offering family -based treatments that can enhance the parent-child relationship and promote recovery by reducing family conflict